2005
DOI: 10.1021/ef049844k
|View full text |Cite
|
Sign up to set email alerts
|

Further Development of a Suspension Fired Reactor To Assess the Relative Performance and Synergistic Effects during the Combustion of Coal Blends

Abstract: An improved suspension-firing reactor has been constructed and a new experimental procedure developed that is able to assess the relative performances of coals and coal blends. The method measures the total combustion time of the samples by measuring the exit gas analysis from the reactor on a continuous basis. The new equipment and procedure overcome some deficiencies that were identified in an earlier suspension-firing method that was based on the extent of burnout of the sample at the end of an arrested com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…4,12 Furthermore, all of the above studies have used a classical "one-factor-at-a-time" methodology to study the effect of operating variables and also the blending ratio. The known shortcomings of this method in identifying the effect of experimental factors and their interactions can be resolved using a statistical design of the experiment based on response surface methodology (RSM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,12 Furthermore, all of the above studies have used a classical "one-factor-at-a-time" methodology to study the effect of operating variables and also the blending ratio. The known shortcomings of this method in identifying the effect of experimental factors and their interactions can be resolved using a statistical design of the experiment based on response surface methodology (RSM).…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to predict the gasification performance of a blend from the performance of its components has not been successful, especially for those fuels that are markedly different in their properties. , Furthermore, all of the above studies have used a classical “one-factor-at-a-time” methodology to study the effect of operating variables and also the blending ratio. The known shortcomings of this method in identifying the effect of experimental factors and their interactions can be resolved using a statistical design of the experiment based on response surface methodology (RSM). , Having fewer experimental runs, detailed identification of experimental factors and their interactions, and the ability to optimize the desired response variables are the main advantages of RSM.…”
Section: Introductionmentioning
confidence: 99%
“…Synergistic Effect for NO Reduction of Co-firing. In coal combustion, it has been reported that a synergistic effect on blending is observed, 40 which is indicated by a difference between the actual performance of the blend and that predicted by the addition of the performance of individual fuels and the blend ratio. In Figure 8, a lower level of NO is shown than expected when co-firing wood and straw, when considering the additive property from co-firing wood/gas and straw/gas in Figure 6.…”
Section: Discussionmentioning
confidence: 99%